Effects to implement the open-innovation coordinative strategies between manufacturer and retailer in reverse supply chain - Sungwook Yoon; Sukjae Jeong (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
A reverse supply chain, as a post-consumption activity, aims at extracting value from products at end of their life cycle (Mafakher and Nasiri, Journal of Cleaner Production 59:185-196, 2013). As well, company's awareness is attracting increasing attention toward sustainable business practices. Open-innovation is a typical example of coordinative activity that a manufacturer should share a profits generated through reverse supply chain with retailer. The aim of this paper provide insights toward open innovation practice in sharing profits between two strategic partners, manufacturer and retailer to maximize an individual profits as well as total profits concurrently in reverse supply chain. For analyzing effects of open innovation strategies, we modeled reverse supply chain environments using system dynamics approach and compared the gap of profits between non-coordinative (decentralized) and coordinative activity. Three cooperative contracts in terms of how to share the cost and profit between two parties are proposed in this paper. Each contract was analyzed according to the following three contract processes. The first stage is that manufacturer proposes contracts to retailer. The second is that retailer evaluates proposed contracts and choices the best contract which can lead to maximize its expected profit. Finally retailer and manufacturer adjust parameters of the best contract for achieving mutual goal of supply chain. Through the experimental results, we discuss best coordinative strategy between manufacturer and retailer in order to maximize a profit in reverse SC.
Keywords: 650; Reverse supply chain; Open innovation system dynamics; Contract implementation procedure